Lévy-distributed fluctuations in the living cell cortex - Shankar Sivarajan; Yu Shi; Katherine M. Xiang; Clary Rodríguez-Cruz; Christopher L. Porter; Geran M. Kostecki; Leslie Tung; John C. Crocker; Daniel H. Reich (Physical Review Research)
The actomyosin cortex is an active material that provides animal cells with a strong but flexible exterior whose mechanics, including non-Gaussian fluctuations and occasional large displacements or cytoquakes, have defied explanation. We study the active fluctuations of the cortex using nanoscale tracking of arrays of flexible microposts adhered to multiple cultured cell types. When the confounding effects of static heterogeneity and tracking error are removed, the fluctuations are found to be heavy tailed and well described by a truncated Lévy α-stable distribution over a wide range of timescales, in multiple cell types. The largest random displacements closely resemble the earlier-reported cytoquakes, but notably, we find these cytoquakes are not due to earthquakelike cooperative rearrangement of many cytoskeletal elements. Rather, they are indistinguishable from chance large excursions of a superdiffusive random process driven by heavy-tailed noise. The noncooperative microscopic events driving these fluctuations need not be larger than the expected elastic energy of single tensed cortical actin filaments, and the implied distribution of microscopic event energies will need to be accounted for by future models of the cytoskeleton.